The Trappings of Home: Young Homeless People's Transitions Towards Independent Living - Brueckner, Martin; Green, M.; Saggers, Sherry (Routledge, 2010)
This paper describes the experiences of young homeless people in Western Australia during their transitions to more permanent accommodation and independent living. For these young homeless people, permanent accommodation provided an opportunity for 'feeling at home' and having a sense of control and stability associated with 'home'. Within this space, these young people wanted to be considered 'normal' home occupiers. In this context, the paper discusses how young homeless people experience and negotiate the social and cultural understandings of home outside socially accepted pathways of leaving the parental home and becoming 'normal' home occupiers themselves. The paper shows how this experience of home, and the potential it offers previously homeless young people, is interrupted by discourses of youth workers, neighbours and society at large, which serve to (re)position them outside the community of 'normal' home occupiers. The findings have implications for both policy and the delivery of services to young homeless people.